The Critic of Literary Values of the Islamic Preach Method Compared Between the Idhah al- Nasyiin Ghalayaini’s Book and The “La Tahzan” - Ali Burhan; Hidayatullah, Agus (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
The Islamic preach is one of the most important means of achieving future generations. The field of this movement does not have every human being, there are certain conditions and controls that the preacher does not spare in order to ensure that he is successful in his preach to study its history and its origins and to learn about its methods, and means. One of the most important means of publishing the preach is writing recently, whether in the form of articles published in newspaper, magazines, or printed books. The first was done by Sheikh Mustafa Al-Ghalayini through newspaper articles and then written in the form of a printed book. The second was carried out by Sheikh Ayd al-Qarni, a Saudi writer whose the most prominent of which is his spectacular book (La Tahzan). The research methodology is about comparing the previous two books by presenting the material contained therein and critiquing it objectively. After this comparison, the researcher discovered that the literary values that affect the success factors in writing preach must be author familiar with theoretical and applied sciences and the need for the writer to observe the laws and controls of writing using a simple, easy to use method supported by clear definite argument, the need for knowledge of the community’s language, its situation and treatment with it the preach in all honesty, starting with the preach of the self and then moving to the wider community, and the complete focus in the preach. And this does not mean leaving the job of the public institution that deal with the community